PENGARUH KOMPETENSI DAN PELATIHAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. POS INDONESIA (PERSERO) CABANG BATURAJA - Priharti, Rr Dimas Veronica; Anggriani, Aprida (STIE DWI SAKTI BATURAJA, 2023)
This research discussed the influence of competency and job training on employees’ productivity at PT. Pos Indonesia (Persero) Baturaja Branch. The data collection technique used in this study was through distributing questionnaires. Total population of 30 employees. The data analysis technique used was Multiple Linear Regression. Based on the results of partial analysis, there was an influence of competency on employees’ work productivity at PT. Pos Indonesia (Persero) Baturaja Branch obtained t count 3.886 with ttable 2.051 because, tcount > ttable or 3.886 > 2.051, then the decision was Ho was rejected and Ha was accepted. Job training variables had an influence on employees’ work productivity at PT. Pos Indonesia (Persero) Baturaja Branch obtained tcount 7.064, because the value of tcount > ttable or 7.064 > 2.051, then the decision was Ho was rejected and Ha was accepted. Simultaneously it was found that there was an influence of competence and job training on employees’ work productivity at PT. Pos Indonesia (Persero) Baturaja Branch with an Fcount of 70.951. This could be seen from the ANOVA table which showed Fcount > Ftable (70.951 > 3.35) then Ho was rejected and Ha was accepted. The coefficient of determination (R2) obtained was 0.840. This showed that the contribution of competence and job training to work productivity was 84.0%, while the remaining 16.0% was influenced by other variables outside of this study, namely mindset, motivation, personality and work environment (Harras, 2020: 389).